Optimising femoral-head osteochondral allograft transplantation in a preclinical model - Brett D. Crist; Aaron M. Stoker; Ferris M. Pfeiffer; Keiichi Kuroki; Cristi R. Cook; Samuel P. Franklin; James P. Stannard; James L. Cook (Journal of Orthopaedic Translation, 2016)
Background/Objective: Osteochondral autografting and allografting of the femoral head have been described as treatments for avascular necrosis without segmental collapse, fracture, osteochondritis dissecans, and tumours. One long-term study reported that 80% of nonsteroid-treated patients had successful outcomes. Most data are compiled from small case reports or series. Although these results are encouraging, to the authors’ knowledge, there is no basic scientific evidence regarding optimal graft source or technique reported in the peer-reviewed literature. The objective of this study was to create a translational canine model to compare femoral-head osteochondral autografts and allografts with respect to safety and efficacy. Methods: With Institutional Animal Care and Use Committee approval, skeletally mature hound-mix dogs (n = 6) weighing >20 kg underwent aseptic surgical implantation of osteochondral grafts using a craniolateral approach to the hip, without dislocation. Three graft options were evaluated: small auto (n = 3), 6-mm-diameter autograft from the trochlear ridge of the ipsilateral knee; small allo (n = 3), 6-mm-diameter fresh (21-day storage) allograft from a size-matched canine femoral head; or large allo (n = 3), 14-mm-diameter fresh (21-day storage) allograft from a size-matched canine femoral head. Small grafts were implanted into the same femoral head of three dogs, and large grafts were implanted alone in the other three dogs. The dogs were allowed unrestricted activity in their runs, and were walked on a leash for 15 minutes 5 times/wk. The outcome measures included functional, radiographic, and arthroscopic assessments at 8 weeks, and functional, chondrocyte viability, and histologic assessments at 6 months after surgery. The pre- and postoperative data were compared for statistically significant (p < 0.05) differences. Based on data from the canine study, four human patients underwent fresh (<28-day storage) osteochondral allografting using large (>30-mm diameter) size-matched femoral-head grafts. The radiographic, quality of life, and functional assessments were captured postoperatively. Results: All grafts had >80% chondrocyte viability at the time of implantation. All grafts showed radiographic evidence for integration into host bone. Small auto and small allo showed significant (p < 0.05) loss in range of motion, chondrocyte viability, and articular-cartilage integrity 8 weeks after implantation, whereas large allo maintained viability and structural integrity throughout the study period. The large-allo dogs maintained full hip range of motion and hindlimb function. A similar type of large allograft (>30 mm) was performed in the four human patients. Due to the defect size, three out of the four human patients required two large allografts at the time of implantation. At the time of this manuscript's acceptance, patient follow-up ranged from 4 months to 18 months. All human patients were full weight-bearing without an assistive device, and showed no evidence of graft failure or progressive arthrosis. Conclusion: These data provide initial translational and clinical evidence for large osteochondral allografts as a potential option for functional resurfacing of full-thickness cartilage defects of the femoral head.